TOPIC: DIACHRONIC AND SYNCHRONIC APPROACHES TO THE STUDY OF THE VOCABULARY OF THE LANGUAGE - Farokhiddinova Robiyakhon Khushnudbek qizi (TADQIQOTLAR, 2025)
Abstract This  article  explores  two  fundamental  approaches  in  linguistic  science:  the diachronic and synchronic methods of studying vocabulary. The diachronic approach considers the historical development of words and traces changes in meaning, form, and  usage  over  time.  In  contrast,  the  synchronic  approach  focuses  on  analyzing vocabulary at a specific moment in time, emphasizing structural relationships within the  language  system.  By  comparing  and  contrasting  these  methods,  the  article demonstrates that both are essential for a comprehensive understanding of language. Furthermore, the study discusses practical applications of these approaches in fields such as lexicography, language teaching, and corpus linguistics.